Penerapan Model Pembelajaran Inquiri Sebagai Upaya Untuk Meningkatkan Prestasi Belajar Pendidikan Agama Hindu - Kartika Buana RN (Cetta: Jurnal Ilmu Pendidikan, 2018)
This research was conducted at SMP Negeri 1 Kerambitan in Grade VIII F semester 1 whose students' ability for Hindu Religious Education subjects is quite low. This study is a classroom action research This objective aims to determine whether the Inquiry learning model can improve student achievement. The method of data collection is the test of learning achievement. The method of data analysis is descriptive. The results obtained from this study is the Inquiry learning model can improve student achievement. This is evident from the results obtained initially 42.31% in the first cycle to 76.92% and in the second cycle to 96.15%. The conclusion obtained from this research is Inquiry learning model can improve learning achievement.